Risk factors for unsuccessful reduction of chronic Monteggia fractures in children treated surgically: a review of 209 cases - WenTao Wang; Zhu Xiong; DianHua Huang; YiQiang Li; YuLing Huang; YueMing Guo; Antonio Andreacchio; Federico Canavese; ShunYou Chen (Bone & Joint Open, 2024)
Aims: To investigate the risk factors for unsuccessful radial head reduction (RHR) in children with chronic Monteggia fractures (CMFs) treated surgically. Methods: A total of 209 children (mean age 6.84 years (SD 2.87)), who underwent surgical treatment for CMFs between March 2015 and March 2023 at six institutions, were retrospectively reviewed. Assessed risk factors included age, sex, laterality, dislocation direction and distance, preoperative proximal radial metaphysis width, time from injury to surgery, reduction method, annular ligament reconstruction, radiocapitellar joint fixation, ulnar osteotomy, site of ulnar osteotomy, preoperative and postoperative ulnar angulation, ulnar fixation method, progressive ulnar distraction, and postoperative cast immobilization. Independent-samples t-test, chi-squared test, and logistic regression analysis were used to identify the risk factors associated with unsuccessful RHR. Results: Redislocation occurred during surgery in 48 patients (23%), and during follow-up in 44 (21.1%). The mean follow-up of patients with successful RHR was 13.25 months (6 to 78). According to the univariable analysis, time from injury to surgery (p = 0.002) and preoperative dislocation distance (p = 0.042) were identified as potential risk factors for unsuccessful RHR. However, only time from injury to surgery (p = 0.007) was confirmed as a risk factor by logistic regression analysis. Receiver operating characteristic curve analysis and chi-squared test confirmed that a time from injury to surgery greater than 1.75 months increased the rate of unsuccessful RHR above the cutoff (p = 0.002). Conclusion: Time from injury to surgery is the primary independent risk factor for unsuccessful RHR in surgically treated children with CMFs, particularly in those with a time from injury to surgery of more than 1.75 months. No other factors were found to influence the incidence of unsuccessful RHR. Surgical reduction of paediatric CMFs should be performed within the first two months of injury whenever possible. Cite this article: Bone Jt Open 2024;5(7):581–591.